The importance of transesophageal echocardiography evaluation in a patient with acute limb ischaemia. Issue 6 (23rd June 2022) - Carrington, Mafalda; Briosa, Alexandra; Quadrado, Marco; João, Isabel
Abstract : This a case of a patient with acute limb ischaemia in whom thorough transesophageal echocardiography (TEE) evaluation depicted a patent foramen ovale and allowed for the detection of a large thrombus arising from an atherosclerotic calcified plaque in the thoracic aorta. We aim to illustrate the importance of performing TEE when systemic emboli are suspected and to not neglect thoracic aorta evaluation when a potential intracardiac cause has been detected.